Reflecting on the Rise and Decline of the South African Defence Industry - Gopaul, Kevin; Van der Lingen, Elma; Oosthuizen, Rudolph (Scientia Militaria - South African Journal of Military Studies, 2024)
The South African Defence Industry has undergone several significant changes during the past six decades, with its current state being deemed unfavourable for continued survivability. To develop a robust understanding of the industry, a review of the scientific literature (and government policies) has been undertaken to chart the trends in the industry through the decades. South African political ideologies in the sixties and seventies resulted in a need for self-sufficiency in defence. By the late eighties, increased military spending resulted in a powerful and capable defence industry, but the end of apartheid and regional conflicts saw an expected sharp drop in the defence budget. The Strategic Defence Package offered some respite in terms of exports, but this has declined in the recent past. The defence budget has remained at a steady low value for two decades, with no real possibility of an increase. To maintain relevance and ensure organisational resilience, the remnants of the South African Defence Industry should use the Defence Industry Strategy as a baseline to develop robust local relationships to drive innovation and foster economic growth, while also strengthening international market share by strengthening unique South African technologies.